Nuclear inelastic scattering studies of a 1D- polynuclear spin crossover complex of Fe(II) urea-triazoles - Wolny, J. A.; Sakshath, S.; Jenni, K.; Scherthan, L.; Auerbach, H.; Wille, H. -C.; Li, A. -M.; Von Malotki, C.; Rentschler, Eva; Schuenemann, V. (Hyperfine Interactions, 2018)
The partial density of vibrational states (pDOS) of the low-spin isomer of the tosylate salt of [Fe(N-Propyl)-N′-(1,2,4-triazole-4-yl-urea)3]2+ was determined by nuclear inelastic scattering experiments performed at 8 K. The pDOS features a rich band structure from 320 to 500 cm−1, characteristic of the low spin state of the complex. Density functional theory calculations (B3LYP/CEP-31G) were used to assign molecular modes to the experimentally observed peak in the pDOS.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Density functional theory; Molecular magnetism; Nuclear inelastic scattering; Spin crossover